Synthesis and preliminary evaluation of benzimidazole derivatives as antimicrobial agents - Klimesová, Vera; Kocí, Jan; Pour, Milan; Stachel, Jirí; Waisser, Karel; Kaustová, Jarmila (European journal of medicinal chemistry, 2002)
A series of 2-alkylsulphanylbenzimidazoles was synthesised and the compounds were evaluated for their in vitro antimicrobial activity. The structures of the compounds were confirmed by 1H-NMR and IR data, and their purity by elemental analysis. Antimycobacterial activities against Mycobacterium tuberculosis and non-tuberculous mycobacteria as well as antifungal activities against Candida albicans, Candida tropicalis, Candida krusei, Candida glabrata, Trichosporon beigelii, Trichophyton mentagrophytes and Aspergillus fumigatus were expressed as the corresponding MIC values. The substances exhibited appreciable antimycobacterial activity, in particular, against non-tuberculous mycobacteria. The activity of the most active compound in the set, 3,5-dinitro derivative 4t, exceeded that of the standard isoniazide against M. kansasii and M. avium. The antifungal activities of the compounds were relatively low. A weak antifungal effect was observed against the dermatophyte Trichophyton mentagrophytes. None of the compounds showed significant inhibitory activity against yeasts.
Keywords: Mycobacterium kansasii; Microbial Sensitivity Tests; Benzimidazoles; Trichosporon; Mycobacterium; mikrobiální testy citlivosti; Anti-Infective Agents; Aspergillus fumigatus; Mycobacterium avium; Magnetic Resonance Spectroscopy; antiinfekční látky; Anti-Bacterial Agents; antibakteriální látky; magnetická rezonanční spektroskopie; Trichophyton; benzimidazoly; Candida